Pengembalian Aset pada Tindak Pidana Korupsi Di Maluku Melalui Uang Pengganti - Fadillah, Astuti Nur; Ubwarin, Erwin; Salamor, Anna (LITIGASI, 2023)
Corruption-related criminal offenses represent a significant challenge in Indonesia. The high number of cases and the financial losses to the state consistently make headlines in the mass media, causing considerable concern among the public. The Indonesian government has made efforts to combat this issue by enacting laws such as Law Number 31 of 1999 on the Eradication of Criminal Acts of Corruption and Law Number 20 of 2001, an amendment to Law Number 31 of 1999. This research employs the Juridical Empirical method, which examines positive law provisions, legal principles, legal doctrines, and legal principles to address the legal issues at hand. The imposition of compensation as a penalty is considered an additional punishment, contingent upon the judge's discretion in evaluating the evidence presented during the trial. The confiscation of assets resulting from corruption can occur through both criminal and civil avenues. In the criminal pathway, the process involves asset tracking, freezing or confiscating assets, asset seizure, return, and handover. Meanwhile, the civil route is utilized if there are still assets owned by the convict suspected to originate from corrupt practices that have not yet been seized by the state. Keywords: Asset Recovery, Corruption Offenses, Compensation Money.